The Potential of Giving Silage Feed Based on Corn Plant Waste (Zea mays) Using Local Microorganisms (Indigenous Microorganism) Against the Percentage of Local Male Non-Carcass Sheep - Bahari Ryansyah Hasibuan; Armyn Hakim Daulay; Hasnudi .; Ma'ruf Tafsin; Yunilas . (Jurnal Peternakan Integratif, 2019)
This study aims to examine the effect of complete corn waste based on silage feed on the percentage of non carcasses on local sheep. The study was conducted at the Laboratory of Animal Biology at the University of North Sumatra in May - August 2018. The design used was a Completely Randomized Design (CRD) with 4 treatments and 3 replications using sheep with an average initial weight of 11.2 ± 0.4 kg. The treatments consisted of four levels of complete silage feed based on corn waste P1 (20%), P2 (40%), P3 (60%), and P4 (80%).The parameters observed were: weight, head, foot, skin, tail, trachea and lungs, liver, heart, blood, and digestive tract.The results showed that complete feed based corn waste silage did not have a significant effect (P> 0.05) on the percentage of non-carcass weight such as skin, tail, trachea and lungs, blood and digestive tract, but gave a non-significant effect on the percentage non carcass weights such as head, feet, heart and liver. The conclusion of complete feed silage based on corn waste can have a significant influence on the internal non carcass (liver and heart) and external (head and foot) parts of male local sheep. In addition it gives a non significant  influence on the non-internal carcass parts (trachea and lungs, blood and digestion) and the external (skin and tail) of male local sheep.